2008
DOI: 10.1002/rcm.3749
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the insecticides thiamethoxam and imidacloprid by zero‐valent metals exposed to ultrasonic irradiation in water medium: electrospray ionization mass spectrometry monitoring

Abstract: The degradation of thiamethoxam (1) and imidacloprid (2), prototype neonicotinoid insecticides bearing a characteristic N-NO2 moiety in their structures, promoted by a number of zero-valent metals (Fe, Sn, Zn) upon ultrasonic irradiation in acidic aqueous solution (pH 2) was investigated. It was verified that thiamethoxam (1) and imidacloprid (2) are quickly and almost completely consumed under these experimental conditions (degradation >90% after a reaction time of 30 min) and that ultrasonic irradiation stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The isotopic patterns of ([M þ 2]) indicated the presence of a chlorine atom in its structure ( Soji c et al, 2012;Zabar et al, 2012). This ion might form in the first step via nucleophilic reaction, where ozone attacks C 7 , who connects with N 8 in the oxadiazinehydro ring via an unsaturated bond with a high positive charge density of 0.66; N 8 atom then connected hydrogen, resulting in a formula of C 8 H 10 ON 4 SCl (de Urzedo et al, 2007;Lopes et al, 2008;Mir et al, 2013;Soji c et al, 2012). Other important fragments were m/z 149/151, 132/134, 115, 101 and 55, which are consistent with P1.…”
Section: Intermediates and Degradation Mechanismmentioning
confidence: 97%
See 1 more Smart Citation
“…The isotopic patterns of ([M þ 2]) indicated the presence of a chlorine atom in its structure ( Soji c et al, 2012;Zabar et al, 2012). This ion might form in the first step via nucleophilic reaction, where ozone attacks C 7 , who connects with N 8 in the oxadiazinehydro ring via an unsaturated bond with a high positive charge density of 0.66; N 8 atom then connected hydrogen, resulting in a formula of C 8 H 10 ON 4 SCl (de Urzedo et al, 2007;Lopes et al, 2008;Mir et al, 2013;Soji c et al, 2012). Other important fragments were m/z 149/151, 132/134, 115, 101 and 55, which are consistent with P1.…”
Section: Intermediates and Degradation Mechanismmentioning
confidence: 97%
“…To minimize its toxicity, an efficient method seems very necessary. We have observed that a few authors have investigated the degradation of THIA by methods such as direct photolysis (de Urzedo et al, 2007), photocatalysis (Mir et al, 2013), methods involving Fe/Fe 3 O 4 composites (de Urzedo et al, 2009), reactive oxidative species , immobilized TiO 2 ( Zabar et al, 2012), and zero-valent metals under ultrasonic irradiation (Lopes et al, 2008). However, studies about degradation of THIA by ozonation were little.…”
Section: Introductionmentioning
confidence: 97%
“…[30][31][32][33][34][35][36][37][38][39][40] In these inquiries, the information provided by the MS (the m/z values of the ionic species) and MS/MS data (the fragmentation profiles of a given mass-selected ion) are meticulously evaluated aiming to propose chemical structures of products (and in some cases transient intermediates) likely formed in the condensed phase. The identification of by-products arising from oxidative treatments, which can be more risky than the own precursors indeed, 42 is an important point that must be taken into consideration for the evaluation of the overall performance of a given process.…”
Section: 2mentioning
confidence: 99%
“…In recent years, a variety of AOPs, but particularly photocatalysis with titanium dioxide (TiO 2 ) and photo‐Fenton treatments, have been used successfully to degrade neonicotinoids . Other, less explored treatments for degrading TMX use UV, ozone (O 3 ) and their combination, or zero‐valent metals under ultrasonic irradiation . Electro‐Fenton oxidation has proved more efficient than Fenton's reagent in removing TMX, but anodic oxidation with a boron doped diamond (BDD) anode at 40 mA cm −2 in 0.1 mol L –1 sodium sulfate (Na 2 SO 4 ) was even more effective in oxidizing TMX [total organic carbon (TOC) conversion was >90% after just 2 h] …”
Section: Introductionmentioning
confidence: 99%